2021
DOI: 10.3390/ijerph182111057
|View full text |Cite
|
Sign up to set email alerts
|

Winning Conditions for the Adoption and Maintenance of Long-Term Healthy Lifestyles According to Physical Activity Students

Abstract: The literature has not yet well documented the relative elements of the adoption of healthy lifestyle habits (HLHs) over the long term. More especially, researchers are calling to complete the corpus with qualitative or mixed estimates that would allow them to better explain the conditions necessary for the adoption or maintenance of HLHs over the long term. The present study seeks to understand the winning conditions for the adoption and maintenance of HLHs. Semi-structured group interviews were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that there may be a link between healthy physical activity habits and nutritional habits [ 7 , 71 ]. This could be because the establishment of a certain healthy lifestyle habit, such as regular physical activity, facilitates the adoption of other healthy lifestyle habits, such as maintaining a healthy diet [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that there may be a link between healthy physical activity habits and nutritional habits [ 7 , 71 ]. This could be because the establishment of a certain healthy lifestyle habit, such as regular physical activity, facilitates the adoption of other healthy lifestyle habits, such as maintaining a healthy diet [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasise that some types of competitive sports might result in negative mental health consequences as a result of bullying and other detrimental social behaviours [ 51 ]. Hence, it is imperative to use prudence when making oversimplified assertions that uniformly affirm sports’ beneficial impact on young individuals’ mental well-being [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several non-binding legal papers have endorsed this request, such as UNESCO’s ‘International Charter of Physical Education, PA and Sport’ [ 21 ] and the WHO’s ‘Global Action Plan on PA’ [ 22 ]. Nevertheless, the application of PA as a therapeutic approach for addressing mental health concerns in teenagers has not been well accepted [ 23 , 24 ]. This can be attributed to the scarcity of empirical investigations and evaluations, namely those concentrating on juveniles and adolescents rather than adults [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the level of physical activity, the results were similar to those from previous research, in which adolescents with a higher AMD showed a higher level of physical activity [ 80 ]. This could be because one of the main determinants for adopting other healthy lifestyle habits during adolescence is the practice of physical activity [ 81 ]. With respect to psychological state, no previous research has analyzed differences in the satisfaction of basic psychological needs according to AMD in the adolescent population.…”
Section: Discussionmentioning
confidence: 99%